Effect of modified complex decongestion therapy in the treatment of breast cancer related lymphedema (改良版综合消肿疗法治疗乳腺癌相关淋巴水肿的效果观察) - LI Qin (李芹); SHI Fan (石帆) (Association of Integrative Nursing, 2021)
Objective To evaluate the effect of modified complex decongestion therapy (CDT) in the treatment of breast cancer related lymphedema (BCRL). Methods Totally 60 patients with BCRL were given complex CDT for four weeks. The degree of limb swelling was evaluated by arm circumference measurement, modified Rodnan skin scores(mRSSs) and the Breast Cancer and Lymphedema Symptoms Experience Index(BCLE-SEI), before intervention, 2 and 4 weeks after intervention respectively. Results The circumference of all measurement sites except for palm horizontal line decreased at 4 weeks after intervention compared with those before intervention (P＜0. 05). The mRSSs and BCLE-SEI scores were reduced at 4 weeks after intervention compared with those before intervention (P＜0. 05). Conclusion The modified CDT is effective in the treatment of BCRL. (目的 评估改良版综合消肿疗法治疗乳腺癌相关淋巴水肿的效果。方法 采用改良版综合消肿疗法对60例乳腺癌术后患侧上肢淋巴水肿患者干预4周, 在干预前、干预2周后、干预4周后, 分别采用上臂周径测量、上肢皮肤硬化程度评分量表(mRSSs)、乳腺癌淋巴水肿症状指数量表(BCLE-SEI)进行效果评价。结果 除掌横纹处周径外, 患侧上肢其他部位周径较干预前缩小, 差异有统计学意义(P＜0. 05)。干预4周后, 患者mRSSs和BCLE-SEI均较干预前下降, 差异有统计学意义(P＜0. 05)。结论 改良版综合消肿疗法对乳腺癌相关上肢淋巴水肿治疗效果良好。)